Assessing the water security effectiveness of integrated river basin management: Comparative case study analysis for lesson-drawing - Ak, Muhammed Yasir; Benson, David (Frontiers in Water, 2022)
Climate change, population growth, over-abstraction and industrial pollution are impacting the security of water resources globally, raising policy relevant questions over the optimality of institutional arrangements for their management. This paper seeks to add to this debate by assessing the effectiveness of integrated river basin management for achieving water security, in two case studies: the Konya Closed Basin in Turkey, and the Kern County Subbasin in California. A modified Institutional Analysis and Development (IAD) framework is employed to compare biophysical, community and governance factors in these cases to show how they influence water security, measured through a dedicated set of indicators. Results show that differentials in water security outcomes between the cases is, in part, related to how organizational rules compel actor participation in planning processes and the degree of coherence between multi-level institutions, particularly inter-agency collaboration. On this basis, the paper then engages with the public policy theory literature on lesson-drawing to assess the potential for policy learning for these specific contexts and other countries. The significance of the study therefore relates to its holistic integration of governance analysis, comparative case design and lesson-drawing for informing future river basin institutional design in achieving effective water security.